Assessment of straylight and the modulation transfer function of intraocular lenses with centrally localized opacification associated with the intraocular injection of gas - Łabuz, Grzegorz; Yildirim, Timur Mert; Khoramnia, Ramin; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2018)
Purpose - To assess the optical quality of intraocular lenses (IOLs) explanted because of opacification after the intraocular injection of gas. - Setting - David J. Apple Laboratory, Heidelberg, Germany. - Design - Experimental study. - Methods - Four hydrophilic acrylic IOLs were studied, each with a centrally localized round opacification pattern associated with the intraocular use of gas. Laboratory analysis included gross examination with a light microscope, followed by alizarin and von Kossa staining. Optical quality was assessed by examining the modulation transfer function (MTF) and straylight. Results were compared with those of a control IOL and normative data for straylight of the crystalline lens. The following parameters were derived from image analysis: opacified surface fraction, light loss in the opacified surface, and the area and number of granules. The relationship between straylight increase and those parameters was studied. - Results - Fine granules were identified on the IOL surface and subsurface. The granules stained positive for calcium, and the MTF levels of 2 IOLs dropped markedly. The other 2 showed relatively minor changes. The straylight was extremely increased in 3 IOLs up to (and above) a level of that of a cataractous lens. A proportional relationship was found between straylight and the morphological parameters from image analysis. - Conclusions - Intraocular lenses with centrally localized opacification have a strong potential for deteriorating optical performance. However, the optical quality might differ depending on the morphology of opacification. A serious straylight increase was found in most of these IOLs, suggesting that affected patients may suffer from glare-related symptoms.